Determinants of MSME Development: a Philanthropy Perspective - Feyza Zahra Anziz; Khusnia Anggraini, Ika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study investigates the influence of spiritual guidance, business mentoring, and capital assistance on the development of micro, small, and medium enterprises (MSMEs) within an Islamic philanthropy-based empowerment program. MSMEs play a vital role in economic growth; however, they continue to face structural challenges, including limited financial resources, inadequate managerial capacity, and restricted market access. This research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a total sample of 45 MSMEs. The findings reveal that business mentoring and capital assistance exert a positive and statistically significant impact on MSME development. Business mentoring enhances managerial capabilities and adaptive capacity, while capital assistance strengthens production capacity and financial resilience. Conversely, spiritual guidance does not demonstrate a statistically significant direct effect, although it contributes to ethical formation and long-term behavioral development. These results underscore the importance of integrating financial and non-financial interventions to design more effective and sustainable MSME empowerment strategies.